Homogenization of China's urban aquatic macrophyte communities: A meta-analytic study. (November 2019) - Ding, Yu; Qian, Shenhua; Wu, Xiaoqi; Zhao, Liang; Lin, Dunmei; Zhang, Jigang; Yang, Yongchuan
Highlights: Urban macrophyte diversity in China is becoming homogenized. The proportion of non-native species used was as high as 30%. Cities in the subtropical zones showed particularly high macrophyte similarity. Abstract: Urbanization results in the extinction of many endemic and specialist species, and has led to the homogenization of biodiversity in global urban ecosystems. The level of biotic homogenization is viewed as an indicator of the impact of urbanization on ecosystems. Using the Jaccard similarity index ( J ), we investigated whether or not the urban aquatic macrophyte communities in China are becoming homogenized at varied spatial scales. We also explored the configurations of greening aquatic macrophyte communities, including species composition, proportion of native versus non-native species, and their life forms for 35 major Chinese cities. We found that pair-wise comparisons of floristic similarity among cities were significantly higher for the urban communities than the natural communities. A high proportion of shared common species among the greening macrophyte communities could be the main explanation of the homogenization of urban macrophyte diversity in China. When grouping the pairs of comparisons by climatic zones, J values were as high as 0.7 for three subtropical zones, indicating that for cities within the same climatic zone, the degree of homogenization in macrophyte diversity could be much higher than the degree of homogenization at the country level. The proportion of non-native species used in urban greening spaces was about 30%, and some non-native invaders such as Eichhornia crassipes and Pistia stratiotes were also frequently seen in the 35 cities. We recommend that new guidelines and regulations be established to guide the selection of aquatic plants during the construction of urban greening facilities. In particular, attention should be paid to the utilization of non-native species for minimizing potential threats to local biodiversity and to mitigate biotic homogenization.